Larantuka Cerdas Ekonomi : Model Pemberdayaan Masyarakat Berbasis Pendidikan Ekonomi di Kelurahan Lewolere, Kecamatan Larantuka - Anita Titu (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The "Larantuka Cerdas Ekonomi" Community Service Program was implemented in Lewolere Village, Larantuka District, with the aim of improving economic literacy, entrepreneurial skills, and community economic independence based on local potential. The background to this activity was the community's low ability to manage finances, develop business plans, and optimally utilize local economic opportunities. The method applied was a participatory approach that included identifying community needs and potential, economic literacy education, entrepreneurship training, business implementation assistance, and evaluation of program success. Data were collected through observations, interviews, focus group discussions, questionnaires, and activity documentation during the 12-week implementation period. Results indicate that the program successfully improved community skills in developing business plans, cost analysis, marketing strategies, and local product innovation. Direct mentoring proved effective in strengthening the application of economics and entrepreneurship, helping participants overcome production and marketing constraints, and increasing economic independence. The "Larantuka Cerdas Ekonomi" model, which integrates economic education, entrepreneurship training, and local wisdom-based mentoring, proved adaptive, contextual, and sustainable. The implications of this program demonstrate that effective community empowerment requires a holistic, participatory approach focused on real-world practice, enabling communities to independently apply economic knowledge. This program can be replicated in other areas with similar social and economic characteristics to sustainably improve community welfare and economic capacity.